Characteristics of tobacco use among secondary school students: a cross-sectional study in a school in Valencia, Spain - Joan Antoni Ribera-Osca; Francisco Carrion-Valero; Francisco Carrion-Valero; Francisco Carrion-Valero; Victor Martin-Gorgojo; Victor Martin-Gorgojo; Yolanda Rando-Matos; Carlos Martin-Cantera; Jose M. Martin-Moreno; Jose M. Martin-Moreno (Frontiers Media S.A., 2023)
IntroductionCigarette smoking is a significant public health problem, and it is essential to work actively with young people to limit the incorporation of this addiction. This study aimed to identify characteristics associated with tobacco use in adolescents in a real setting.MethodsEpidemiologic, cross-sectional study including secondary school students aged 12-17 years in the 1st, 2nd, and 3rd grades of "Joan Fuster High School" in the city of Sueca, Valencia (Spain). An anonymous, self-administered questionnaire was used to collect data on demographics, cigarette smoking history, alcohol consumption, nicotine dependence, and exposure to parental cigarette smoking.ResultsThe final sample of individuals surveyed included 306 students (50.6% females) with a median age of 13 years. The prevalence of cigarette smoking was 11.8% (13.5% in females and 9.9% in males). The mean age of cigarette smoking onset was 12.7 ± 1.6 years. Ninety-three students (30.4%) were repeaters, and 114 (37.3%) reported alcohol consumption. Significant factors associated with tobacco use were being a repeater (odds ratio [OR] 4.19, 95% confidence interval [CI] 1.75-10.55, p = 0.002), alcohol consumption (OR 4.06, 95% CI 1.75-10.15, p = 0.002) and parental cigarette smoking (OR 3.76, 95% CI 1.52-10.74, p = 0.007).DiscussionAn operational profile of features associated with tobacco consumption was identified in the presence of parental cigarette smoking, alcohol consumption, and poor academic performance. Consideration of these factors could be useful in the operational design of cigarette smoking cessation interventions for young people in a context where there is a great need for better prevention and control of cigarette smoking.